2023
DOI: 10.1136/lupus-2022-000870
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Fli-1 impacts the expression of CXCL13 and regulates immune cell infiltration into the kidney in MRL/lpr mouse

Abstract: ObjectiveFriend leukaemia virus integration 1 (Fli-1) regulates chemokine/cytokine expression and thus plays an important role in the development of lupus nephritis. Chemokine CXC ligand 13 (CXCL13) is a chemokine that promotes the formation of ectopic lymphoid structures and has been reported to be associated with the pathogenesis of lupus nephritis. The relationship between Fli-1 and CXCL13 is unknown. This study aims to elucidate whether Fli-1 impacts CXCL13 expression and contributes to the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In Fli-1 +/− MRL/lpr mice, there was low level of CCL2, CCL3, CCL4, CCL5, STAT3, CXCR3, CXCR5, CXCL9, CXCL10, CXCL13, SRY-related HMG box4 (Sox4), neuraminidase 1 (NEU1), NEU3, and each of the major lactosylceramide (LacCer) species (C16, C22, C24, and C24:1), total LacCer in the kidney relative to those in controls. 1,2,[23][24][25][26] There were reduced serum levels of total IgG, IgG1, and IgG3, CXCL13, IL-6, IL-17A, anti-dsDNA, decreased urine protein levels in lupus mice, and serum concentrations of anti-dsDNA were positively related to IL-6 levels. 2,21,23,25,27 Interestingly, there were severe glomerular inflammation in Fli-1 +/+ group when compared to that in Fli-1 to levels of CCL4, CCL5 from kidney in Fli-1 +/− group.…”
Section: Fli-1 and Lupus Developmentmentioning
confidence: 96%
See 2 more Smart Citations
“…In Fli-1 +/− MRL/lpr mice, there was low level of CCL2, CCL3, CCL4, CCL5, STAT3, CXCR3, CXCR5, CXCL9, CXCL10, CXCL13, SRY-related HMG box4 (Sox4), neuraminidase 1 (NEU1), NEU3, and each of the major lactosylceramide (LacCer) species (C16, C22, C24, and C24:1), total LacCer in the kidney relative to those in controls. 1,2,[23][24][25][26] There were reduced serum levels of total IgG, IgG1, and IgG3, CXCL13, IL-6, IL-17A, anti-dsDNA, decreased urine protein levels in lupus mice, and serum concentrations of anti-dsDNA were positively related to IL-6 levels. 2,21,23,25,27 Interestingly, there were severe glomerular inflammation in Fli-1 +/+ group when compared to that in Fli-1 to levels of CCL4, CCL5 from kidney in Fli-1 +/− group.…”
Section: Fli-1 and Lupus Developmentmentioning
confidence: 96%
“…1,2,[23][24][25][26] There were reduced serum levels of total IgG, IgG1, and IgG3, CXCL13, IL-6, IL-17A, anti-dsDNA, decreased urine protein levels in lupus mice, and serum concentrations of anti-dsDNA were positively related to IL-6 levels. 2,21,23,25,27 Interestingly, there were severe glomerular inflammation in Fli-1 +/+ group when compared to that in Fli-1 to levels of CCL4, CCL5 from kidney in Fli-1 +/− group. 25 Moreover, migration of the inflammatory cells (CD3 + IL-17A + T cells, CD19 + B cells, CD11b + CXCL13 + cells) in Fli-1 +/− group in response to CCL2, CCL4, CCL5 reduced in relative to the migration in control mice.…”
Section: Fli-1 and Lupus Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, transcriptomic studies of LN kidneys in MRL/lpr and BXSB models showed increased cxcl13/cxcr5 along with upregulated expression signature associated with TLS formation (63), suggesting a role of CXCL13/CXCR5 in TLS formation in LN. In animal studies, BAFF, TLR7 signaling, and Fli-1 have also been suggested to play a role in TLS formation (54, 65,71). These and other molecular and cellular mechanisms associated with TLS formation in lupus are described in Table 3.…”
Section: Potential Mechanisms Underlying Tls Formation In Lnmentioning
confidence: 99%
“…(4) When wild-type mice with nephritis are treated with anti-IL-17F neutralizing antibodies, histological damage scores are significantly reduced compared to those treated with isotype antibody [ 12 ]. (5) IL-17F-deficient lupus mice exhibit reduced mortality and albuminuria compared to regular lupus mice [ 13 ]. (6) RORγt, a crucial transcription factor in Th17-cell development, has been shown to promote CGN [ 14 ].…”
Section: Introductionmentioning
confidence: 99%